The Technical Value of Magnetic Resonance Imaging and Ultrasonography in Identifying Characterization of Ovarian Cysts - Ali Hani Karim; Mahmood Radhi Jobayr; Lamyaa F.A. Al-Barram (Institute of Medico-legal Publications Pvt Ltd, 2021)
An accurate diagnosis of ovarian cysts is of utmost importance to determine the timely treatment to preservefertility.We sought to determine the effectiveness of ultrasonography and MRI modalities for diagnosing themost common ovarian lesions and differentiate between benign and malignant lesions in order to guidepatients to appropriate treatment. This study was conducted on 94 women, the age group between 14-70years, in the period of January 2020 to October 2021. Were all women suffering from abdominal pain,swelling, nausea or vomiting and bleeding and irregular menstrual cycle. Was suspected clinically in thepresence of lesions in the ovary was confirmed by tests of ultrasound and magnetic resonance. The entirecases were subjected to transvaginal and transabdominal ultrasound and magnetic resonance imagingto assess ovarian lesions in terms of content (somatic, cystic solid), nodules, septal characteristics, wallthickness, vascular lesion and ascites.In USG, there were 16% cases of malignant ovarian lesion and 84%cases had benign lesions. MRI reports showed that 10.6% cases had malignant ovarian lesions and 89.4%cases had benign lesions. Findings of USG with HPE have 100.0% sensitivity, 89.1% specificity and 91.07%diagnostic accuracy. In MRI findings with HPE have 100.0% sensitivity, 100% specificity, and 100.0%diagnostic accuracy. MRI had high specificity and more accuracy value in terms of diagnostic performancethan USG. The ultrasonography diagnostic value in case of characterization of adnexal mass lesion wassignificantly lower than in the MRI.